Psychographics segmentation in Mulu National Park - Samdin, Zaiton; Abdul Aziz, Yuhanis (IDOSI Publications, 2015)
Market segmentation is a crucial tool in ecotourism, which is used to identify and categorise the tourists. This paper describes the profile of tourists to Mulu National Park (MNP) based on the types of psychographic segmentation (activities, interest and opinion) in ecotourism. In general, the purpose of this paper is to present affective segmentation of tourists to MNP. It was found that tourists in MNP are heterogeneous which indicated that tourists’ characteristics are diverse in many aspects. Tourists with different background and characteristic of age, gender, level of income and education level are different in their preferences and taste. The result discusses several implications of market segmentation for nature tourism product promotion, development and marketing strategy.